HUBUNGAN BIMBINGAN BELAJAR PENDIDIKAN AGAMA ISLAM MELALUI MODUL DAN MOTIVASI BERIBADAH DENGAN PRESTASI BELAJAR SISWA MTs HIDAYATUL ISLAMIYAH KARAWANG - Prisuwantoro Prisuwantoro; Yayat Suharyat; Asep Dudin Abdul Latif (Lembaga Penelitian Dan Pengabdian Masyarakat Institut Agama Islam Sultan Muhammad Syafiuddin Sambas Kalimantan Barat, 2021)
Relationship of Islamic Religious Education Guidance Through.Modules and Motivation for Worship on Student Achievement at MTsS Hidayatul.Islamiyah Karawang Thesis, Graduate School of Islamic Education Masters. Islamic University 45 Bekasi, West Java. 2021 There are many efforts to maintain student achievement during the pandemic, among others, by maximizing learning activities, adding appropriate media to serve student learning, holding modules to help students learn even by providing offline, online earning, all of which are expected to be able to boost learning achievement and motivation. However, the facts show differently, many students have not maximized distance learning participation, students find it difficult to learn because the material is not optimally acceptable, even though the learning carried out has been assisted by modules. This research is to find out: The relationship between PAI tutoring through Modules with PAI Students' Achievements; The relationship between PAI tutoring through Modules and Students' worship motivation; and Simultaneous relationship between student tutoring through modules and motivation to worship with student achievement. The forms of tutoring services for students include providing orientation to students which contains information about school goals, curriculum, adjustment, learning methods, and school organizational structures, providing information on appropriate learning methods for students during lessons at school or independently. At home, both in groups and individually. The method used is a quantitative survey technique. Used to obtain data that occurred in the past or present, about beliefs, opinions, characteristics, behavior, variable relationships and to test several hypotheses about sociological and psychological variables from samples taken from certain populations, at MTs Hidayatul Islamiyah Jatibaru Jatisari Karawang as many as 79 Sample. It was concluded that there was no significant relationship between the PAI Learning Guidance variable with the Module (X1) and the PAI student learning achievement (Y).Sig value 0.14 is greater than 0.005 (0.14 > 0.05) and the calculated T value is greaterthan t table (1,479 < 1,9812) Ho is accepted. The Sig value for X2 Worship Motivationtowards Y PAI learning achievement is 0.770 > 0.005 and the t value is 0.293 < from Ttable 1.9812, H2 is rejected. Furthermore, there is no simultaneous relationshipbetween the variables X1 (Learning Guidance with Modules) and Variable X2(Students' Worship Motivation) with PAI Learning Achievements, the significant value of H3 is rejected, which means that there is no simultaneous effect of X1 and X2 on Y,the amount is only 3.5%. Implications: Module guidance needs to be maintained, coupled with other creativity that can improve student achievement. Suggestions are expected to be able to encourage the academic community to be able to make variouslearning plans that make students' achievements increase.